Actors, others, simulacra: a Deleuzean minority report on the early modern Dubrovnik stage. Issue 1 (2nd January 2019) - Feldman, Lada Cale
ABSTRACT: A playwright in the minor and marginal culture of renaissance Ragusa, Marin Držić (1508–1557) has often been compared to Shakespeare, despite the obvious impossibility of influence in either direction. There is however an aspect of Držić's legacy which has received a scarce critical interest in Croatia, although it could also be discussed along the lines of Shakespeare studies: early modern Dubrovnik acting practice, culture, and style. Držić's actual and meta-theatrical treatment of acting will here be interpreted through the lenses of Gilles Deleuze's essay 'One less manifesto'. In this essay, Deleuze expands his notion of 'the minor', arguing for a kind of acting practice that would rely on variation, movement, becoming, and a perpetual linguistic deformation, forces that hinder absorption into the discourse of 'the major'. I will further suggest that Marin Držić's exposure of the anti-theatrical prejudice of his contemporaries – clothed in a mock-version of Genesis and elaborated in the prologue of his comedy Uncle Maroje – could be read as an exemplary inversion of Plato's method of argumentation that makes a Deleuzian case for the actor as the ultimate, troubling Other, the simulacrum of true being, a promiscuous and metamorphic kin of marionettes, animals, and women.